Struktura professional'noi podgotovlennosti spetsialista po vostochnym edinoborstvam - Litmanovich, A. V. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The aim of this research was the revealing of features rendering influence to the training process of specialists in martial arts. 62 specialists with the various experience of trainers activity and skill level have taken part in the research 60 % of the respondents have the highest education and the experience of work more than 5 years. As a result of the specialists' opinions analysis (based on the data of questionnaire) the three-level model of specialists in martial arts professional preparedness were determined. The first level is the fundament of activity, its basis. The second level is a psychological-pedagogical preparedness. The third level reflects special theoretical preparedness.